A qualitative study of patient experiences of care in integrated behavioral health and primary care settings: more similar than different. Issue 5 (7th February 2018) - Davis, Melinda M; Gunn, Rose; Gowen, L Kris; Miller, Benjamin F; Green, Larry A; Cohen, Deborah J
Abstract: Integrated behavioral health and primary care is a patient-centered approach designed to address a person's physical, emotional, and social healthcare needs. Increasingly, practices are integrating care to help achieve the Quadruple Aim, yet no studies have examined, using qualitative methods, patients' experiences of care in integrated settings. The purpose of this study was to examine patients' experiences of care in community-based settings integrating behavioral health and primary care. This is a qualitative study of 24 patients receiving care across five practices participating in Advancing Care Together (ACT). ACT was a 4-year demonstration project (2010–2014) of primary care and community mental health centers (CMHCs) integrating care. We conducted in-depth interviews in 2014 and a multidisciplinary team analyzed data using an inductive qualitative descriptive approach. Nineteen patients described receiving integrated care. Both primary care and CMHC patients felt cared for when the full spectrum of their needs, including physical, emotional, and social circumstances, were addressed. Patients perceived personal, interpersonal, and organizational benefits from integrated care. Interactions with integrated team members helped patients develop and/or improve coping skills; patients shared lessons learned with family and friends. Service proximity, provider continuity and trust, and a number of free initial behavioral health appointments supported patient access to, and engagement with, integrated care. In contrast, patients' prior experience, provider "mismatch, " clinician turnover, and restrictive insurance coverage presented barriers in accessing and sustaining care. Patients in both primary care and CMHCs perceived similar benefits from integrated care related to personal growth, improved quality, and access to care. Policy makers and practice leadership should attend to proximity, continuity, trust, and cost/coverage as factors that can impede or facilitate engagement with integrated care. Abstract : Patients felt cared for when their physical, emotional, and social circumstances were addressed. Patients reported benefits from integrated care related to personal growth and improved quality/access to care, regardless of initial setting type.